Eksploitasi Hutan sebagai Kejahatan Ekologis dalam Perspektif Hukum Islam: Forest Exploitation as an Ecological Crime: An Islamic Law Perspective - Jumarni Dalle; Inda Sari Palinrungi; Rahman (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
Forest exploitation is a serious issue that directly impacts environmental degradation, public safety, and the sustainability of natural resources. To date, forest exploitation has largely been understood as an administrative and policy-related issue in natural resource management, resulting in limited legal accountability. This article aims to analyze the legal status of forests within the perspective of Islamic law and to formulate a framework of criminal liability for forest exploitation that harms public interests. This study employs a normative juridical approach through library research, utilizing primary sources such as the Qur’an and Hadith, as well as secondary sources including literature on fiqh jināyah and legal maxims. The findings indicate that forests in Islamic law can be classified as part of public ownership (milkiyyah ‘āmmah), whose management constitutes a state trust for public welfare. Forest exploitation that causes environmental damage and social harm can be analyzed as an act involving elements of fasād fī al-arḍ and, through legal reasoning (istinbāṭ), can be classified as a ta‘zīr offense. The novelty of this study lies in the expansion of criminal liability, which not only applies to individuals and corporations as direct actors but also extends to the state in cases of administrative negligence and abuse of authority. Thus, Islamic criminal law provides an adaptive framework for addressing modern ecological crimes based on the protection of public welfare.